Relationship between reverse logistics and green supply chain management in retail in Gauteng - Gxumisa, Nosipho Brigalia (My University, 2016)
Reverse logistics and green supply chain management are concepts that are relatively new to South Africa, compared to more developed countries. The aim of the research was to understand how South African companies are approaching these concepts and to determine whether a relationship exists between reverse logistics and green supply chain management in the retail sector in Gauteng. Due to the lack of data of companies using reverse logistics and green supply chain management in Gauteng, a qualitative research methodology was used to gather more information on the topic. Thirteen interviews were conducted with experienced individuals representing some of the largest and most well-established retail companies in Gauteng. The results from the interviews and literature demonstrated that companies who want to implement a successful reverse logistics strategy must establish and adopt reliable processes to follow. Without proper record keeping, companies will be overwhelmed and be unable to track returns, resulting in unhappy customers. Green operations can also have economic benefits, as demonstrated by most of the respondents. The literature mentions financial spin offs from remanufacturing of used products resulting in secondary markets and companies in South Africa need to focus more on creating these markets. As customers and consumers become more aware of sustainability issues, it is important that companies be seen to be practicing good environmental principles and caring for the sustainability of the communities that they serve. Companies that have positive environmental strategies improve their competitive position and grow their market share.
MBA
Keywords: Business logistics -- South Africa.Sustainability -- South Africa.Remanufacturing -- South Africa.